Assembly and comparative analysis of the complete mitogenome of Rubus chingii var. suavissimus, an exceptional berry plant possessing sweet leaves - Shi, Yujie; Chen, Zhen; Jiang, Jingyong; Wu, Wenwu; Xin, Yue; Zeng, Wei (Frontiers in Plant Science, 2024)
Rubus chingii var. suavissimus is a special berry plant of Rubus in the Rosaceae family. Its leaves contain high-sweetness, low-calorie, and non-toxic sweet ingredients, known as rubusoside. As a medicine and food biofunctional plant, it is a combination of “tea, sugar, and medicine.” In this study, the complete mitogenome of R. chingii var. suavissimus was successfully assembled and annotated based on PacBio HiFi sequencing technology. The mitogenome of R. chingii var. suavissimus was a typical master circle structure, spanning 432,483 bp and containing 34 unique protein-coding genes (PCGs), 20 tRNAs, and 3 rRNAs. The majority of these PCGs was subjected to purifying selection, and only one gene (ccmB) showed sign of positive selection. The mitogenome of R. chingii var. suavissimus contained a large number of repeats, and the homogeneous fragments transferring between plastid genome and mitogenome, with a total of 55 pairs of mitochondrial plastid sequences (MTPTs), and the total size was 56,913 bp. Comparative analysis showed that the non-coding region in the mitogenome of R. chingii var. suavissimus had undergone frequent rearrangements during evolution, but the coding region was still highly conserved. Furthermore, the maximum likelihood and Bayesian inference phylogenetic trees were reconstructed of 10 shared PCGs in 36 plant species. The topological structures of two phylogenetic trees were consistent with the APG IV classification system and had high support rates. In general, this study clarifies the mitogenome of R. chingii var. suavissimus and provides valuable insights into the genetic evolution of the Rosaceae family.